A Política de Financiamento da Rede Pública Municipal de Ensino de Cascavel, Paraná, (2013 a 2021) - Silva, Érica Teixeira da (2023)
This dissertation has as its research topic the financing of the Municipal Public Education Network of Cascavel, Paraná (PR) from 2013 to 2021. The study aimed to investigate and understand the Brazilian State basic education funding policy and, specifically, how this policy has been implemented in funding the Municipal Public Education Network of Cascavel (PR) from 2013 to 2021. The resources designated for financing municipal public education networks come from the municipality’s fundraising and from Constitutional and Legal Transfers from the Union and of the state of which the city is a part. The central matter that steered the investigation of the issue was the following: Which federal entity (the Union, the state of Paraná, or the municipality) contributed the most to funding the Cascavel (PR) municipal public school network between 2013 and 2021? The central hypothesis guiding this work is that the city of Cascavel (PR), among all other federated entities, was the one that contributed, through its own resources, with the greatest budgetary efforts to finance basic education in the Municipal Public School Network of Cascavel (PR) from 2013 to 2021. To achieve the proposed goal we carried out a quantitative and qualitative study. In the research process, we took Budgetary Balances as a starting point: Fiscal and Social Security Budgets, Statements of the Execution of Expenditure by Function/Subfunction, Statements of Income and Expenditure on Maintenance and Development of Education (MDE), the School Census database, the reports of the institutions in agreement with the Municipal Public Administration of the National Fund for the Development of Education (FNDE) from 2013 to 2021, Protocols: nº 61.150/2021, Municipal Planning and Management Secretariat (Seplag), nº 47.616/2021 and nº 46.308/2022, Municipal Education Secretariat (Semed). As a theoretical basis for analysis we propose, based on the Dialectical Method and the historical approach, to not consider the multiple determinations in order to grasp the historical movement of the matter under investigation. It was concluded that from 2013 to 2018, the state of Paraná, in proportional and financial terms, was the federal entity that contributed the most resources to funding the Cascavel (PR) Municipal Public Education Network. However, from 2019 onwards, in financial and percentage terms, the municipality of Cascavel (PR) became the main federal entity responsible for providing resources to fund the maintenance and development of the Cascavel (PR) Municipal Public Education Network